Conceptual Kinematic Design and Performance Evaluation of a Chameleon-Like Service Robot for Space Stations. (6th March 2015) - Ceccarelli, Marco; Li, Hui; Carbone, Giuseppe; Huang, Qiang
In this paper a conceptual kinematic design of a chameleon-like robot with proper mobility capacity is presented for service applications in space stations as result of design considerations with biomimetic inspiration by looking at chameleons. Requirements and characteristics are discussed with the aim to identify design problems and operation features. A study of feasibility is described through performance evaluation by using simulations for a basic operation characterization.